Analisis Faktor Penyebab Kesulitan Belajar Siswa dalam Pembelajaran Matematika Kelas XI IPS 4 SMA Negeri 2 Sungai Limau - Irma Dian Pratama; Dewi Yuliana Fitri; Lita Lovia (STKIP PGRI Sumatera Barat, 2021)
This research is motivated by the low learning outcomes of students' mathematics. Low learning outcomes are characteristics of students experiencing obstacles or obstacles during the learning process. This study aims to describe and analyze the factors that cause students' learning difficulties in mathematics. The sample of this study amounted to 32 students of class XI IPS 4 SMA Negeri 2 Sungai Limau. The type of research used is descriptive research with a quantitative approach. The instrument used is a learning difficulty questionnaire, interview sheets and documentation to strengthen the results of the questionnaire answers. The data analysis technique of this research is the analysis of questionnaires and interviews. The results of this study indicate that: 1) internal factors that affect learning difficulties are described as follows, in the indicator of readiness in learning as much as 71.8% in the category of very influential on the learning process, on motivation indicators as much as 29% in the category of being quite influential in the learning process , on the indicator of interest as much as 53% with the category influential in the mathematics learning process and the health indicator as much as 50.6% with the category having an effect on learning mathematics. 2) external factors that affect learning difficulties in mathematics are as follows, indicators of family factors in learning as much as 37.5% with a category that is quite influential on the mathematics learning process, on school indicators as much as 51.5% with categories that affect the online learning process and on environmental indicators community as much as 39.6% with the category quite influential on the student learning process.